Understanding identity construction among deaf adolescents and young adults: implications for the delivery of person and family-centered care in audiological rehabilitation - Hlayisi, Vera-Genevey; Sekoto, Lieketseng Victoria (Frontiers in Rehabilitation Sciences, 2023)
The provision of holistic person and family-centered care in the audiological rehabilitation of adolescents and young adults (AYA) requires in-depth consideration of identity construction. The purpose of this research study was to describe the lived experience of identity construction among deaf AYA. The thoughts, perceptions, and feelings of AYA on their identity and the processes underlying the construction of identity, with a focus on navigating disability, social relations and roles, community assimilation and self-perception were explored. Methods: A qualitative interpretive phenomenological approach was adopted. Participants were a purposive sample of 5 AYA, aged 15 to 19 years. Participants had moderate to profound deafness and were enrolled in schools for the deaf where they partook in semi-structured phenomenological conversations, detailing their lived experiences with identity construction. Results: The superordinate themes of creating a self-concept, belonging, stress and being deaf emerged from participants' narratives. Identity construction occurs concurrently at several levels. At the personal level, AYA create self-conceived ideals of who they are. At relational level, identity is fostered through person-to-person and person-to-group interactions. At societal level, AYA navigate inherent challenges with hearing impairment and their positionality as deaf individuals. Conclusions: Understanding the nuances of identity construction gives insights for further research and highlights the self-ascribed identity domains and related psychosocial variables that appeal to person and family-centered care, uncovering opportunities and barriers to successful delivery. Findings have implications for the transitional care of deaf AYA that is responsive to their needs.